2019
DOI: 10.3390/molecules24122336
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclic Diterpenoids from Euphorbiaceae as A Source of Potent and Selective Inhibitors of Chikungunya Virus Replication

Abstract: Macrocyclic diterpenoids produced by plants of the Euphorbiaceae family are of considerable interest due to their high structural diversity; and their therapeutically relevant biological properties. Over the last decade many studies have reported the ability of macrocyclic diterpenoids to inhibit in cellulo the cytopathic effect induced by the chikungunya virus. This review; which covers the years 2011 to 2019; lists all macrocyclic diterpenoids that have been evaluated for their ability to inhibit viral repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 64 publications
1
30
0
Order By: Relevance
“…Furthermore, with the comparison of the biological results of 307, 309, and 311 to those of 308, 310, and 318, it was demonstrated that favorable following trend in activity at C-8 is: benzoyloxy group [ H & hydroxy group (Hasan et al 2019). Remy and Litaudon (2019) have published a review on anti-CHIKV activity of eighty diterpenoids covering the years 2011 to 2019. Twenty-five jatrophanes have been investigated for their ability to inhibit viral replication.…”
Section: Mdr Reversing Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, with the comparison of the biological results of 307, 309, and 311 to those of 308, 310, and 318, it was demonstrated that favorable following trend in activity at C-8 is: benzoyloxy group [ H & hydroxy group (Hasan et al 2019). Remy and Litaudon (2019) have published a review on anti-CHIKV activity of eighty diterpenoids covering the years 2011 to 2019. Twenty-five jatrophanes have been investigated for their ability to inhibit viral replication.…”
Section: Mdr Reversing Activitymentioning
confidence: 99%
“…Existence of an acetyl group at position 2 within the 9,14-dioxojatropha-dienes and the 2-methylbutyryl group in the 9-oxojatropha-dienes series, proved to be deleterious for anti-CHIKV activity. Furthermore, the C-8 substitution influences the activity of jatrophanes (tiglyloxy [ benzoyloxy [ acetyloxy & isobutyryloxy) (Remy and Litaudon 2019). Esposito et al (2016) isolated six new jatrophane esters including euphodendroidins J-O (456-461) from the E. dendroides.…”
Section: Mdr Reversing Activitymentioning
confidence: 99%
“…PKCs are a multigene family of related serine/threonine kinases that are involved in many signal transduction pathways and cellular responses. PKCs play a role in a multitude of cellular functions such as cell mitogenesis, differentiation and apoptosis, smooth muscle contraction, platelet aggregation, tumor-modulation, and anti-HIV activity ( 198 ). PKCs are classified into three sub-families with different isoforms depending on the way of their activation.…”
Section: Antivirals Against Chikungunya Virusmentioning
confidence: 99%
“…Recently a study reviewed the anti-CHIKV activity of about 80 naturally occurring macrocyclic diterpenes originating from the Euphorbiaceae plant family and about 30 commercially available natural diterpenoids ( 198 ) ( Table 1 ). Some of these compounds have also been tested against other alphaviruses, like SFV or SINV.…”
Section: Antivirals Against Chikungunya Virusmentioning
confidence: 99%
“…Euphorbia comprises a great diversity of plants from the spurge family (Euphorbiaceae), containing more than 2000 species [ 6 ]. The Euphorbiaceae family comprises a great chemical variety that includes a wide range of diterpenoids with therapeutic activities such as antiproliferative, anti-inflammatory, antiviral, and immunomodulatory properties [ 7 , 8 , 9 , 10 , 11 ]. In fact, some diterpenoids from Euphorbia esula L. showed antimalarial [ 12 ], pro-inflammatory, and antitumor activities against multidrug-resistant (MDR) and non-resistant human gastric cancer cells [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%